Identification of rice cultivars tolerant to aluminum toxicity by multivariate technique - Ferreira, Reinaldo de Paula; Cruz, Cosme Damião; Sediyama, Carlos Sigueyuki; Fageria, Nand Kumar (Pesquisa Agropecuaria Brasileira, 1995)
The objetive of the present study was to evaluate 20 rice genotypes in solution culture for their tolerance and susceptibility to Al toxicity grown in 20 ppm of Al concentration. Growth characteristics evaluated were: root length, root and shoot dry weight, total seedling dry weight, and seedling length measured ten days after growing in the nutrient solution. The multivariate technique used was that proposed by Anderson (1958) and according to this technique upland rice genotypes were found. to be tolerant to Al toxicity, whereas genotypes of irrigated rice were grouped as susceptible to Al toxicity.